Hattiesburg : an American city in black and white - Sturkey, William (The Belknap Press of Harvard University Press, 2019)
In this rich multigenerational saga of race and family in Hattiesburg, Mississippi, William Sturkey reveals the personal stories behind the men and women who struggled to uphold their southern "way of life" against the threat of desegregation, and those who fought to tear it down in the name of justice and racial equality.--